An update of fixed drug eruptions in Singapore. (10th December 2014) - Heng, Y.K.; Yew, Y.W.; Lim, D.S.Y.; Lim, Y.L.
Abstract Background Fixed drug eruptions (FDE) are most commonly caused by antibiotics and non‐steroidal anti‐inflammatory drugs (NSAIDs). The list of causative drugs changes with time and prescribing patterns but there has been no recent data on FDE seen in an outpatient setting in Singapore. Objective We aimed to evaluate the epidemiology, clinical features and causative drugs in patients with FDE in Singapore. Methods We performed a retrospective chart review of all patients seen with suspected FDE in the National Skin Centre, Singapore between 2008 and 2012. Using criteria adapted from the WHO‐UMC causality assessment criteria, patients were classified into categories of definite (confirmed with patch test or drug provocation test), probable (causative drug identified based on patient's history), possible (clinically consistent but unable to identify causative drug) or unlikely FDE. Results We reviewed the charts of 126 patients who were seen for suspected FDE. Ten patients (7.0%) were classified as having definite FDE, 52 patients (41.3%) probable FDE, 61 patients (48.4%) possible FDE and three patients (2.4%) unlikely FDE. Clinical features were similar to those described in previous studies. Among the 62 patients with definite or probable FDE, etoricoxib was the most common cause (24 patients, 38.7%). Other common causes included paracetamol, other NSAIDs and doxycycline. Antihistamines caused FDE in three patients. Conclusion Etoricoxib was the most frequent cause of FDE in our study. Other NSAIDs, paracetamol and doxycycline remain common causes of FDE but we caution that antihistamines, such as cetirizine, should also be considered.